Effects of implementing feeding, breeding and a herd health program on the performance of boer goat breeding farm in Sabah - Salisi, Mohd Shahrom (2011)
The ruminant sector in Malaysia contributed 9% of the ex-farm value and the goat industry is relatively small in Malaysia, with approximately 247,000 – 350,000 heads mainly by smallholders. Currently, the goat industry supplies only 8% of the local demand for chevron. Therefore, Malaysia is spending approximately RM5.8 million (USD1.7 million) annually to import livestock products to fulfil the demand. In trying to reduce the bill for importation of livestock products, the Malaysian government decided in 2005 to enhance the livestock industry, particularly the cattle and goat industries. The first step toward enhancing these industries is to increase the cattle and goat populations to approximately 1 million head by 2010 through a breeding program respectively. Thus, importation of goats from various goat-producing countries, particularly from Australia to increase the number of breeders, particularly Boer goats had been initiated since 2006.Culling and mortality are important factors that determine the success of a livestock farm. Losses from mortality and culling were at the rate of 36.6% and 14.5%, respectively while the causes of goat morbidity and mortality are usually related to the mismanagement. Therefore, a herd health program is extremely important to improve management. This study formulates, implement and evaluate a herd health program, which include feeding regimen, disease control and breeding protocol on the performance of a Boer goat farm in Sabah. Feeding regimen included feeding of an average of 2kg of cut grass/goat/day and supplemented with goat pellet at 300g, 400g and 500g/goat/day for maintenance, growth and pregnant and lactating goats, respectively. The disease control included brucellosis, mannhemiosis, haemonchosis , colibacillosis and coccidiosis while breeding program involved introduction of bucks at appropriate time. The average monthly mortality in 2005 was significantly (p<0.05) higher (10.1%) compared to that in 2006, 2007 and 2008 which was 3.8%, 3.9% and 2.5% respectively. It was found that implementation of herd health program significantly (0<0.05) increased the average body weight gains in both adults and kids from 1.8g per kids and 0.6g per adults in 2006 to 3.7g per kids and 2.2g per adults in 2008. The percentage of adults with body scoring of <3 was significantly (p<0.05) reduced from 82.3% in 2006 to 77.6% in 2007 and 4% in 2008. Similarly, the annual mortality rate was significantly (p<0.05) reduced from 6.5% among kids and 58.2% among adults in 2006 to 12.1% among kids and 10.4% among adults in 2007, and to 9.1% among kids and 1.1% among adults in 2008. Therefore, it was concluded that implementation of herd health program significantly improved the survival and performance of goats.Following implementation of new feed and feeding regimen, there were significant (p<0.05) improvement in the body score of breeder females. There was consistently significant (p<0.05) yearly increase in the percentage of females with body score of >3 from prior to implementation (56% and 73% in 2006 and 2007, respectively) and post-implementation (81%, 98% and 99% in 2008, 2009 and 2010, respectively). Following implementation of the new feeding regimen, the average birth weight had shown significant (p<0.05) improvements to 3.25 kg in 2008, 3.32 kg in 2009 and 3.43 kg in 2010. Prior to the implementation, average birth weights were only 2.93 kg in 2006 and 2.91 kg in 2007. Similarly, following implementation of breeding program in January 2008, there was general improvement of pregnancy rate among Boer goats in the farm. The pregnancy rate in (the treated group) had significantly (p<0.05) increased to 48%, 75% and 86% in 2008, 2009 and 2010, respectively compared during pre-implementation (control group) with 14% pregnancy rate of and 32% in 2006 and 2007, respectively. The farm had successfully managed to achieve the targeted pregnancy rate of more than 80% in year 2010. The kidding rate had significantly (p<0.01) improved to 145% in 2008 and 2009 and 153% in 2010. This indicate that in 2008 and 2009, a breeder doe produced an average of 1.45 kids while an average of 1.53 kids was produced by a doe in 2010. During the pre-implementation period (control group), kidding rates were only 121% in 2006 and 122% in 2007 and had achieved 150% or 1.5 kidding rate in 2010, 2 years after the implementation of breeding program (control group).There was an increasing pattern of annual expenditure and income in the 5-year study period of 2006 to 2010. The annual expenditure and income patterns led to an increasing pattern of the annual gross income with decreasing losses and eventually showed profit in 2010. Prior to the implementation of the herd health program, the total expenditure in 2006 was significantly (p<0.05) lower than post-implementation periods of 2008, 2009 and 2010. This was mainly due to the significant (p<0.05) increase in the operational costs following implementation of disease control, feeding regime and breeding programs. The capital, mainly associated with buying of new breeders, was significantly (p<0.05) increased in 2008 but remained low once the breeders were stabilized. Following implementation of herd health program, however, the income showed significant (p<0.05) increase from 2008 and remained high until the end of study period in 2010. The main source of the income remained the sale of goats, particularly post-implementation period between 2008 and 2010. In conclusion, the implementation of feeding , herd health and breeding programs in this study has provided significant positive impact on livestock performance such as reducing the average monthly and annual mortality of livestock, increasing the average weight gain of the animal, increasing the percentage of adults with body score> 3, pregnancy rates and birth rates of livestock. Although expenses (operating costs) is increasing but the gross profit through the sale of livestock and the reduction of livestock death losses in this farm has been achieved following the execution of all programs undertaken in this study.